2020
DOI: 10.3847/1538-4357/ab7b68
|View full text |Cite
|
Sign up to set email alerts
|

Distortion of Magnetic Fields in BHR 71

Abstract: The magnetic field structure of a star-forming Bok globule BHR 71 was determined based on near-infrared polarimetric observations of background stars. The magnetic field in BHR 71 was mapped from 25 stars. By using a simple 2D parabolic function, the plane-of-sky magnetic axis of the core was found to be θ mag = 125 • ± 11 • . The plane-of-sky mean magnetic field strength of BHR 71 was found to be B pos = 8.8 − 15.0 µG, indicating that the BHR 71 core is magnetically supercritical with λ = 1.44 − 2.43. Taking … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…This leads to the formation of filamentary structures perpendicular to the magnetic field (or perpendicular to the plane of the paper in Figure 14). This mechanism of dense-filament formation was discovered by Inoue & Fukui (2013) and Vaidya et al 2013; see also Arzoumanian et al 2018 andKandori et al 2020 for observational supports). We emphasize that the filaments formed by this mechanism lie perpendicular to the magnetic field, at least when they are first created.…”
Section: Structure Formation In the Interface Layersupporting
confidence: 57%
“…This leads to the formation of filamentary structures perpendicular to the magnetic field (or perpendicular to the plane of the paper in Figure 14). This mechanism of dense-filament formation was discovered by Inoue & Fukui (2013) and Vaidya et al 2013; see also Arzoumanian et al 2018 andKandori et al 2020 for observational supports). We emphasize that the filaments formed by this mechanism lie perpendicular to the magnetic field, at least when they are first created.…”
Section: Structure Formation In the Interface Layersupporting
confidence: 57%
“…The morphology of the B-fields is affected by gravity (resulting in a well-known hour-glass shape; Ewertowski & Basu 2013), and regulated by the supersonic gas motion as proposed by Inoue & Fukui (2013). The latter seems to be frequently observed, e.g., deformation of B-field geometry in M16 (Pattle et al 2018), Orion-A (Tahani et al 2019), Musca filament (Bonne et al 2020a(Bonne et al , 2020b, and BHR 71 bipolar outflow system (Kandori et al 2020). Using simulations, Abe et al (2021) demonstrated that a shock with a velocity of ∼7 km s −1 is able to wrap the B-fields.…”
Section: Introductionmentioning
confidence: 98%
“…Although lower-mass, BHR 71 appears to be somewhat analogous to CB 54. However, Kandori et al (2020) mapped the magnetic field in BHR 71 using SIRPOL NIR polarimetry at the IRSF, finding the field to be significantly distorted from the mean plane-of-sky field direction in the region. They ascribe this distortion to an interaction between the globule and a large-scale shock (cf.…”
Section: Comparison With Other Regionsmentioning
confidence: 99%